Implementation of Green HRM Practices in the Hospitality Industry: A Cross-Country Comparative Study (International Forum of Researchers and Lecturers, 2024)
This study aims to explore and compare the implementation of Green Human Resource Management (GHRM) practices in the hotel industry in India and Indonesia. Using a comparative case study approach, data were collected through semi-structured interviews with HR managers and employees from six hotels in both countries. Thematic analysis was used to identify patterns in the adoption of GHRM practices such as recruitment and selection, training and development, performance management, and employee engagement. The results show similarities in the types of GHRM practices adopted, but with varying levels of implementation. Contextual factors such as stakeholder pressure, top management commitment, and cultural values were identified as key drivers of these differences. This study contributes to the literature by providing empirical evidence on the implementation of GHRM in developing countries and highlights the role of contextual factors in shaping the adoption of these practices.